COD/sulfate ratio does not affect the methane yield and microbial diversity in anaerobic digesters. (15th May 2019) - Cetecioglu, Zeynep; Dolfing, Jan; Taylor, Jessica; Purdy, Kevin J.; Eyice, Özge
Abstract: Anaerobic digestion of organic matter is the major route of biomethane production. However, in the presence of sulfate, sulfate-reducing bacteria (SRB) typically outcompete methanogens, which may reduce or even preclude methane production from sulfate-containing wastewaters. Although sulfate-reduction and methanogenesis can occur simultaneously, our limited understanding of the microbiology of anaerobic digesters treating sulfate-containing wastewaters constrains improvements in the production of methane from these systems. This study tested the effects of carbon sources and chemical oxygen demand-to-sulfate ratio ( C O D / S O 4 2 − ) on the diversity and interactions of SRB and methanogens in an anaerobic digester treating a high-sulfate waste stream. Overall, the data showed that sulfate removal and methane generation occurred in varying efficiencies and the carbon source had limited effect on the methane yield. Importantly, the results demonstrated that methanogenic and SRB diversities were only affected by the carbon source and not by the C O D / S O 4 2 − ratio. Graphical abstract: Image 1 Highlights: Microbial diversity in anaerobic digesters with high-sulfate wastewater was studied. The C O D / S O 4 2 − ratio did not affect the diversity of methanogens and sulfate-reducers. The microbial diversity and metabolism were mainly affected by the carbon source. The presence of sulfate affected methanogenesis in butyrate- and TMA-incubations.